Knowledge and Anxiety Levels about the Spread of Covid-19 Cases in the Community in Patihan Village, Madiun City - Vena Agustin Pravitasari; Riska Ratnawati (Journal of Health Science and Prevention, 2021)
Coronavirus is a disease that can cause respiratory tract infections. The addition of cases that are increasing every day makes people more worried about their health. The purpose of this study was to analyze the relationship between knowledge and the level of anxiety about the spread of Covid-19 cases in Patihan Village, Madiun City. The researcher used quantitative research with observational survey method with cross sectional approach. In analyzing the data, the researcher used univariate analysis as a frequency measurement tool and bivariate analysis used Kendall's tau-b test statistics. The population in the study was 1373 families, the sample was 32 families. The method used is purposive sampling. The results of the bivariate test showed that there was a significant relationship between the independent variable and the dependent variable, which obtained a value (Sig. = 0.034). The level of knowledge is sufficient to have a moderate level of anxiety as many as 5 respondents (55.5%), the level of knowledge is sufficient with a level of severe anxiety as many as 4 respondents (44.5%), while the level of knowledge is good with a moderate level of anxiety as many as 4 respondents (17.4% ), and the level of knowledge is good with the level of severe anxiety as many as 19 respondents (82.6%). There is a significant relationship between knowledge and the level of anxiety about the spread of Covid-19 cases in the community in Patihan Village, Madiun City. Suggestions for further researchers can conduct qualitative research methods with a case control approach on respondents who have comorbidities.